Introduction: Documenting, Theorising, Mapping and Testing the Plurality of SE Models in Central and Eastern Europe - Defourny, Jacques; Mihály, Melinda; Nyssens, Marthe; Adam, Sophie (Social Enterprise in Central and Eastern Europe, 2021)
This introduction presents an overview of the key concepts discussed in the subsequent chapters of this book. The book describes three main types of former socialist states: countries that were ruled by the Union of Soviet Socialist Republics (USSR), such as Armenia and the Baltic States; the so-called “allied states” of the USSR, such as Czechoslovakia, Hungary and Poland; and post-Yugoslav countries, such as Croatia and Serbia. It argues that the most oppressed socialist states were the former republics of the USSR, such as Armenia and the Baltic states. The book focuses on the fact that all the three types of state socialism had a negative influence on the cooperative movement and on formal civil society in CEE countries. It describes a top–down approach aiming to establish an Social Enterprise sector is probably not likely to succeed if it does not meet with genuine social entrepreneurial initiatives and a collective identity in the field.